Water insecurity is human: why social science must be at the core of water security research and practice - Wutich, Amber (Frontiers in Water, 2025)
Many water scholars believe we are at an inflection point in which new approaches to water research and management are needed, and I agree. Water insecurity is fundamentally driven by human behavior and is socially determined. To address this, the emerging science of water security can build on well-established and theoretically-robust findings from social science. Foundational work establishes the formative role of human social structures in producing water insecurity, particularly for populations experiencing poverty, racial/ethnic minoritization, and political exclusion. While infrastructural and legal/regulatory reforms are essential to advance water security, they have failed vulnerable populations in patterned, predictable ways globally. New research highlights how social and engineered infrastructures that are hybrid, modular, adaptive, and decentralized can improve water security for the most vulnerable populations. However, reliance on such systems is inherently a feature of unjust, inequitable water governance. Social scientists have a valuable role to play in explaining these dynamics, addressing water system failures, and developing more equitable water solutions.